Association between serum total bilirubin levels and 28-day all-cause mortality after intracerebral hemorrhage - Qiu, Dachang; Li, Guangwei; Dong, Yongfei (Frontiers in Neurology, 2025)
BackgroundIntracerebral hemorrhage (ICH) is associated with high mortality and morbidity rates. Although some studies have indicated a correlation between serum bilirubin levels and ICH severity, evidence of the relationship between serum total bilirubin (TBIL) and ICH outcomes remains lacking.MethodsA total of 914 patients from the Medical Information Mart for Intensive Care IV database met the eligibility criteria and were included in the study. The patients were categorized into two groups based on whether they survived for 28 days following admission to hospital. The association between serum TBIL levels and 28-day survival in patients with ICH was investigated using Spearman’s correlation analysis and restricted cubic splines. The effect of serum TBIL levels on survival time and rate in the 28-day period was analyzed using Kaplan–Meier curves and restricted mean survival times. Univariate Cox regression, least absolute shrinkage and selection operator regression, and multivariate Cox regression were used to identify risk factors associated with 28-day all-cause mortality. Finally, subgroup analysis was performed to verify the stability of the association between serum TBIL levels and 28-day all-cause mortality in patients with ICH.ResultsA negative relationship was revealed between TBIL levels and survival (p < 0.001, correlation = −0.174). Restricted cubic spline analysis revealed a nonlinear link between mean serum TBIL levels and 28-day all-cause mortality (p for nonlinear = 0.001). Patients with ICH and higher serum TBIL levels had significantly reduced survival times and rates compared with those with lower serum TBIL levels (p < 0.001). Serum TBIL level was identified as a significant risk factor for 28-day all-cause mortality in patients with ICH (hazard ratio [95% confidence interval] = 1.121 [1.063–1.182], p < 0.001). Subgroup analyses revealed that the assessed variables had no influence on the association between serum TBIL levels and 28-day all-cause mortality.ConclusionHigher serum TBIL levels are associated with a greater risk of mortality within 28 days in patients with ICH, whereas lower serum TBIL levels are associated with prolonged survival.